Arah Kebijakan Kerja Sama Pertanian Indonesia di Kawasan Asia Pasifik (Forum Penelitian Agro Ekonomi, 2019)
In the current globalization era, it can no longer be inevitable the importance of cooperation among countries to realize peace and mutual prosperity. One of the growing international collaborations in the Asia Pacific region is Association of South East Asian Nations (ASEAN) and Asia Pacific Economic Cooperation (APEC). The idea of the agricultural cooperation importance is one of the efforts to respond to various challenges in free trade and globalization era where each country in the Asia Pacific region has its advantages and disadvantages. This paper aims to describe the readiness of Indonesia’s agriculture and reviewing several international cooperation that built in the Asia Pacific region. With the use of the analysis framework based on the theories of international cooperation, showed that Indonesian agricultural sector still requires effort to empowerment because dominated by the small-scale businesses with limited capital and innovative technology, respectively. Most of the agricultural export products are also still needs the exertion of increase of its competitiveness. The cooperation in the Asia-Pacific region is very prospective. Trade and investment cooperation are more open in the Asia Pacific region will open market opportunities for agricultural products Indonesia thereby potentially encourage high economic growth and to increase the standard of life of the people of Indonesia and other countries in the Asia Pacific region. To create new opportunities and new markets in the Asia Pacific region, needed the policy direction covering four interrelated matters, namely how to improve access of agricultural commodity markets, increase investment, develop technical cooperation and strengthen diplomacy function as a factor of facilitating Indonesia facilitators in facing many agriculture collaborations for today and the future.AbstrakDi era globalisasi seperti sekarang ini, tidak dapat lagi dielakkan pentingnya menjalin kerja sama antarnegara dalam rangka mewujudkan perdamaian dan kesejahteraan bersama. Salah satu kerja sama internasional yang berkembang saat ini di kawasan Asia Pasifik adalah Association of South East Asian Nations (ASEAN) dan Asia Pasific Economic Coorperation (APEC). Pemikiran akan pentingnya menjalin kerja sama, khususnya di bidang pertanian merupakan salah satu upaya merespon berbagai tantangan di era globalisasi dimana masing-masing negara di kawasan Asia Pasifik memiliki kelebihan dan kekurangannya. Tulisan ini bertujuan menganalisis kesiapan pertanian Indonesia serta mereview beberapa kerja sama internasional yang dibangun di kawasan Asia Pasifik. Dengan kerangka analisis yang didasarkan pada teori-teori kerja sama internasional, diperoleh gambaran bahwa sektor pertanian Indonesia masih memerlukan upaya pembenahan/ dan pemberdayaan karena usaha pertanian saat ini masih didominasi oleh usaha dengan skala kecil, modal yang terbatas, dan penggunaan teknologi yang masih sederhana. Sebagian besar produk ekspor pertanian juga masih memerlukan upaya peningkatan daya saing. Meskipun demikian prospek kerja sama di kawasan Asia-Pasifik sangat menjanjikan. Kerja sama perdagangan dan investasi yang lebih terbuka di kawasan Asia Pasifik akan membuka peluang pasar bagi produk pertanian Indonesia sehingga berpotensi mendorong pertumbuhan ekonomi yang tinggi, serta meningkatkan standar hidup masyarakat Indonesia dan negara lainnya di kawasan Asia Pasifik. Untuk menciptakan peluang baru serta pasar baru di kawasan Asia, dibutuhkan adanya strategi mencakup empat hal yang saling terkait yakni bagaimana meningkatkan akses pasar, meningkatkan investasi, mengembangkan kerja sama teknik (technical cooperation) serta penguatan fungsi diplomasi pertanian sebagai faktor pelancar Indonesia dalam menghadapi berbagai kerja sama di bidang pertanian saat ini dan ke depan.